Teaching for Transformation: Master of Social Work Students Identify Teaching Approaches That Made a Difference - Damianakis, Thecla; Barrett, Betty; Archer-Kuhn, Beth; Samson, Patricia; Matin, Sumaiya; Ahern, Christine (Journal of transformative education, 2025)
Transformative learning captures the process by which students engage in their learning, experience a change in perspective, of themselves or society, and then enact their new understanding. The purpose of this 4-year, four-cohort study was to identify the transformative learning experiences of Master of Social Work students and specific student engagement strategies they felt made a difference in preparing them for professional practice. Six focus groups (n = 40) were conducted using established focus group methodology. All focus groups were audio recorded, professionally transcribed verbatim, and subject to qualitative content analysis. Students identified six themes in student engagement strategies that facilitated their transformative learning, including transformative aspects of the curriculum, experiences with peers, qualities in their relationships with faculty that fostered critical reflection, a sense of identity, and mentoring. This study will help educators better identify teaching strategies to engage students in their personal and professional transformative learning.